Building Women Homebased Workers' Organizations in Turkey - Gülsüm Coşkun (Global Labour Journal, 2009)
A slightly different version of this article was presented in the session titled as 'Organizing Women Homebased Workers in the Era of Globalization' by RC 44, Labour Movements, in the First ISA Forum of Sociology, 5-8 September 2008, Barcelona, Spain. It is an attempt to describe the main points of the history of the organizational struggles of women homebased workers in Turkey by a woman homebased worker herself. The article mainly focuses on the relationships between women’s workload and the living and working conditions of homebased workers; organizational forms and strategies of homebased workers; organizational levels and their interactions; and in order to gaining visibility, the importance of building alliances.